Assessment Of Infection Control Knowledge And Practice Compliance Among Nursing Staff In Emergency And Intensive Care Units (The Review of Diabetic Studies, 2025)
Healthcare-associated infections (HAIs) are a significant problem to healthcare systems across the world and especially in hospitals that are considered high-risk areas such as emergency departments (EDs) and intensive care units (ICUs). Nurses are at the core of applying infection prevention and control (IPC). The purpose of the study was to evaluate the level of knowledge regarding infection control, adherence to infection control measures, as well as the significance of the institutional support of the nursing staff working in EDs and ICUs. The study was a cross-sectional descriptive correlational study with 178 nurses. The questionnaire of the structured questionnaire with a five-point Likert scale was used to collect data. Pearson correlation analysis and descriptive statistics were done. The findings showed that there was a high rate of knowledge (M = 4.51), compliance (M = 4.50) and institutional support (M = 4.48). There was a high positive correlation between compliance and the knowledge on infection control (r =.62, p